The Two Faces of Informal Employment in Romania - Drechsler, Denis (OECD Development Centre Policy Insights, 2008)
Informal employment is a widespread phenomenon in Romania and a key challenge for the country's development. Policies should target two distinct groups: those who voluntarily opt out of the formal system and those with no alternative. Transforming people's attitudes towards the state and strengthening their trust in public institutions is key